Risky Behaviours among Adolescent Students of Pokhara Valley: A School-Based Cross-sectional Survey - Ranabhat, Kamal; Thapa, Kanchan; Shahi, Shubhadra; Rana, Himalayan (Journal of Nepal Health Research Council, 2020)
Background: Adolescence is the period of physical and mental vulnerabilities where health risk behaviours are common due to their experimental nature and decision-making power. A higher prevalence of risky behaviours among adolescents has been reported globally which resulted in adverse effects on health and wellbeing. The present study aims to explore the overall prevalence of health risk behaviours among adolescents.Methods: This study was conducted in 2014 using the WHO guideline of a Global School-Based Student Health Survey (GSHS) in the Pokhara valley of Nepal using a stratified clustered sampling technique. A descriptive study was conducted among 1190 adolescent school students of the valley. A self-administered questionnaire was used for data collection. The data were analysed using SPSS for descriptive statistics.Results: The response rate of the participants was 95.35%. The prevalence of the current use of tobacco, alcohol, and drug was 15.9%, 17.1%, and 4.1% respectively. The mean age of first use of tobacco, alcohol, and drug was found 14.07±1.82, 14.19±1.78, and 15.52±1.61 years respectively. Two third (66.4%) of the participants reported having sexual intercourse one or two times within the last 12 months. Among them, 21.4 % reported no use of condoms during sexual intercourse. The mean age of first sexual intercourse was 14.69±1.56 years. Similarly, 42.2% reported being injured in the past 12 months of study.Conclusions: The study shows a higher prevalence of health risk behaviours among adolescents. Tobacco, drug, alcohol use, and risky sexual activities were initiated at a younger age.Keywords: Adolescent health; health risk behaviours; Nepal; substance abuse.